Unraveling of Multifactorial Etiology and Risk Factors of Severe Anemia HB ≤ 6 g/dL - Razia, Easha-Tur-; Khan, Sara Arshad; Awan, Abdul Khalid (Indus Journal of Bioscience Research, 2024)
Background: Anemia is an alarming worldwide health condition affecting individuals from modernized and countries that underdeveloped, with significant implications for human health and socio-economic development.Aims: This research aimed to find the primary risk factors linked with severe anemia (HB ≤ 6 g/dL) and assess the relative contribution of different factors, including nutritional status, chronic diseases, infections, and genetic factors.Methodology: A cross-sectional study investigated the fundamental causes and risk factors of disease anemia (HB≤ 6 g/dL). The following study was conducted at the Abbas Institute of Medical Sciences, Muzaffarabad AJK Pakistan. The data was collected through a nonprobability purposive sampling technique. Multivariate analysis was applied using logistic regression to identify specific risk factors for severe anemia.Results: The mean age of the patients was 34.2 years (SD 10.8), with 60% from low socioeconomic status. The mean iron level was 30.4 (SD 12.5) and the mean vitamin B12 level was 190.3 pg/mL (SD 2.3). 46.7% had a history of chronic diseases, with 20.0% having type 2 diabetes and 13.3% having renal diseases. 26.7% were suffering from infections. Chronic disease history significantly increases the risk (OR 2.50, p=0.004).Conclusion: The study population had low hemoglobin and iron levels, with a high proportion of patients having chronic diseases. Severe anemia was significantly associated with low iron levels and Vitamin B12 deficiency, chronic diseases, and infections, increasing the risk of severe anemia